WHY FACEBOOK IS NOT A GATEWAY TO NEWS CONTENT - Palmer, Marie (AoIR Selected Papers of Internet Research, 2021)
Over the past fifteen years, the emergence of intermediaries has transformed the circulation of news content. Social media platforms and news aggregators have become main gateways to news content. However, they don’t circulate news but snippets of existing news content. This article focuses on why those snippets are identified by users as news. Drawing on social semiotics, this study uses the concept of genre - as a tacit and conventional system of categorisation of texts or discursive practices (Neale, 1980), which provides clues regarding how to interact with a text in a specific cultural situation (Martin, 1984)- to understand the complex nature of the snippet. Using a multimodal analysis of a series of over 150 Facebook news posts, this article argues that the design of Facebook posts uses horizontal and vertical intertextuality, to generate a socially endorsed comment on news. Therefore, Facebook cannot really by defined as a gateway to news content but rather as an intertextual commenter.